2009
DOI: 10.1073/pnas.0901367106
|View full text |Cite
|
Sign up to set email alerts
|

Major flowering time gene, FLOWERING LOCUS C , regulates seed germination in Arabidopsis thaliana

Abstract: FLOWERING LOCUS C (FLC) is a major regulator of flowering responses to seasonal environmental factors. Here, we document that FLC also regulates another major life-history transition-seed germination, and that natural variation at the FLC locus and in FLC expression is associated with natural variation in temperaturedependent germination. FLC-mediated germination acts through additional genes in the flowering pathway (FT, SOC1, and AP1) before involving the abscisic acid catabolic pathway (via CYP707A2) and gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
286
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(299 citation statements)
references
References 62 publications
10
286
2
1
Order By: Relevance
“…None of the seeds obtained germinated in the absence of GA (at least 200 seeds were tested). These results underscore the advantages of having used the ft background, which was recently shown to improve germination (28). The ft mutation caused a delay in flowering time in the quintuple phytochrome mutant background (Fig.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…None of the seeds obtained germinated in the absence of GA (at least 200 seeds were tested). These results underscore the advantages of having used the ft background, which was recently shown to improve germination (28). The ft mutation caused a delay in flowering time in the quintuple phytochrome mutant background (Fig.…”
Section: Resultsmentioning
confidence: 66%
“…Previous failure could be due to the fact that the seeds of the quintuple mutant do not germinate if GA is not added to the substrate. Here, we initially obtained the quintuple phytochrome mutant in the ft mutant background, which has recently been shown to improve germination (28).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, life history traits that comprise complex phenotypes such as phenology (Armbruster, Pélabon, Bolstad, & Hansen, 2014; Murren, 2012; Peiman & Robinson, 2017), may have both genetic and functional linkages. For example, in Arabidopsis thaliana , the FLOWERING LOCUS C (FLC) gene regulates flowering time and mediates germination time by affecting seed dormancy through a pleiotropic genetic correlation (Chiang et al., 2009). Simultaneously, in A. thaliana and many flowering plants, the sequential nature of expression of phenological traits results in functional linkage, as the timing of flowering affects traits later in development such as fruit maturation and seed dispersal (Donohue, 2009; Galloway & Burgess, 2009; Lacey & Pace, 1983; Lacey, Roach, Herr, Kincaid, & Perrott, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, our model of Arabidopsis phenology is at present silent about the factors that influence the timing of germination, even though recent studies have shown that certain genes in the flowering time network are also involved in seed dormancy and germination behaviour (Heschel et al 2008;Chiang et al 2009). Both maternal environmental factors such as temperature ) and genetic factors (Alonso-Blanco et al 2003;Holdsworth et al 2008;Chiang et al 2009) affect germination behaviour in this species. Despite such advances, we still know relatively little about the natural seasonal and climatic conditions that are permissive for germination (see also review in Donohue 2009).…”
Section: (D) Model Limitations and Future Extensionsmentioning
confidence: 99%